KEBERHASILAN YANG DICAPAI OLEH BAPAK YUKARI SEBAGAI PENGELOLA USAHA JUAL BELI KELAPA SAWI - Erik Laorensyah; Sofino Sofino (Jurnal Pendidikan Sepanjang Hayat, 2021)
The research objective was to describe the success of Mr. Yukari's palm oil trading business in Tanjung Tebat Village, Bunga Mas District, South Bengkulu Regency. There were three participants. This research is a qualitative research. Data collection techniques using interview techniques, observation and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data used the triangulation technique. The results showed that the establishment of Mr. Yukari's business in 2014 with a capital of Rp. 150,000,000. The number of purchases of palm oil is currently 30 tonnes per day. Mr. Yukari's turnover is currently Rp. 6,000,000 per day. Mr. Yukari's current business profit is IDR 75,000,000 per month. Mr Yukari's assets are currently four transport cars, five trucks, and 13 hectares of oil palm land. The current number of employees is eleven employees. The external problem in Mr. Yukari's business is purchasing price competition. Mr. Yukari's solution is by considering price competition as a common thing and Mr. Yukari remains in his stance.